An Examination of Preservice Teachers' Simulated Classroom Assessment Practices - Bachor, Dan G.; Baer, Markus R. (Alberta Journal of Educational Research, 2001)
The comments made by 127 preservice teachers (PTs) in the Faculty of Education, University of Victoria as they compiled portfolios on three hypothetical grade 5 children are examined. The PTs were asked to record their comments in the form of a journal throughout the term. At the end of the term the PTs' comments were collected, transcribed, and the resultant data analyzed using Atlas/ti. The data were analyzed to examine the types of decisions the PTs made about the hypothetical children. Two main patterns of decisions were taken by the PTs. Most seemed to follow a fairly logical set of procedures, formulating criteria to evaluate the assignments and then applying them. A few appeared to make judgments that may have been unsound, however, commenting on the children's quality of life or designating them as having special educational needs when the evidence presented did not support such conclusions.